Learning by Exporting or Self-Selection into Exporting? - Kiendrebeogo, Youssouf (Taylor and Francis, 2021)
This paper explores the export-productivity relationship using firm-level data from Egypt over the 2003–2008 period. Previous studies using data from developed countries suggest that self-selection is the main driver of the exporter premium. Using a propensity-score matching difference-in-difference approach, we find that both labor productivity and total factor productivity are significantly higher for exporters than for non-exporters. On average, labor productivity and total factor productivity are, respectively, 43% and 61% higher for exporting firms than for domestically-oriented firms. Accounting for the level of development of destination countries, we find that this export premium is due to a learning-by-exporting process rather than just a self-selection of more productive firms into exporting. In contrast to exporters to OECD countries, exporters to Non-OECD countries self-select into export markets, signaling the importance of the technical assistance from OECD buyers.